KOMUNIKASI ORGANISASI SEBAGAI MOBILITAS SOSIAL - Ninik Hidayati (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
Communication within an organization is a common practice for managing relationships between individuals and groups. In an organization is determined by the person's position on the structure and Hierarchy within the organization. Today the organization assigns roles to each member so that the roles are then operationalized into tasks and functions. The process of cooperation in implementing change or acceleration of change within the organization is called